Celebrating Inclusion and Diversity: Utilizing Multimodality and Multilingualism to Enhance Children's Leadership - Zulystiawati, Zulystiawati; Ibrahim, Moh. Syahrun (Program Studi Magister Pendidikan Anak Usia Dini, 2026)
This paper investigates how multimodality and multilingualism enhance children's leadership skills through celebrating inclusion and diversity. It examines how these strategies nurture essential leadership qualities such as cultural awareness, respect, and empathy among young learners. By embracing various modes of learning and communication—visual, auditory, kinesthetic, textual, and digital—alongside multilingual environments, the study provides a holistic framework for leadership development. The research demonstrates how these approaches improve children's communication abilities, cultural competence, cognitive flexibility, and adaptability, supported by reflective discussions and diverse role models. The study argues that these strategies create inclusive environments that enrich language skills and prepare children to become empathetic leaders in a multicultural world. Parents and educators can implement practical approaches at home and in educational settings, including storytelling, cultural immersion, and interactive multilingual games, to develop empathetic, innovative, and effective leaders capable of thriving in a diverse world